2019
DOI: 10.1111/joss.12492
|View full text |Cite
|
Sign up to set email alerts
|

Sweeter together? Assessing the combined influence of product‐related and contextual factors on perceived sweetness of fruit beverages

Abstract: It is well‐known that multiple sensory cues influence flavor perception and liking. The present study aimed to combine and compare the relative influences of product‐related and contextual factors on taste perception and liking, with a focus on the perception of sweetness. Participants tasted samples of the same base fruit beverage with one of three different levels of added aroma, while the contextual cues (either visual or auditory) were displayed simultaneously using iPads. The results revealed that both ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…In theory, however, mixed results have been shown in the existing literature on the influence of taste-specific visual cues on flavour perception. Some studies have indicated a significant influence of taste-congruent visual cues on product liking [2,14,24] while other studies have not reported this result [5,77]. Additionally, a recent study showed the existence of crossmodal correspondences between physical warmth and light colours [78].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, however, mixed results have been shown in the existing literature on the influence of taste-specific visual cues on flavour perception. Some studies have indicated a significant influence of taste-congruent visual cues on product liking [2,14,24] while other studies have not reported this result [5,77]. Additionally, a recent study showed the existence of crossmodal correspondences between physical warmth and light colours [78].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, researchers are now starting to assess how, for example, the visual attributes of the environment, combined with the auditory atmosphere, can influence a consumer's behaviour (e.g., Sester, Deroy, Sutan, Galia, Desmarchelier, Valentin, & Dacremont, 2013;Spence, Puccinelli, Grewal, & Roggeveen, 2014;Spence, Velasco, & Knoeferle, 2014;Wang, Mielby, Thybo, Bertelsen, Kidmose, Spence, & Byrne, 2019;Wansink & Van Ittersum, 2012;. Researchers have also started to assess different ways to effectively present music as part of a food/drink product's identity.…”
Section: Product-extrinsic Multisensory Contributions To Food Perceptmentioning
confidence: 99%
“…What we hear affects what we taste, no matter whether we realise it or not (and the evidence suggests that mostly we do not, e.g., see North, Hargreaves, & McKendrick, 1997, 1999Zellner, Geller, Lyons, Pyper, & Riaz, 2017). In fact, there is now an extensive body of literature highlighting the impact of the sounds that may be associated with food preparation (Wheeler, 1938; see Knöferle & Spence, in press, for a recent review), food packaging (i.e., being opened; , 2017a; see Wang & Spence, 2019, for a review), and food consumption (e.g., Youssef, Youssef, Juravle, & Spence, 2017;Zampini & Spence, 2004; see Spence, 2015a, for a review), on people's sensory-discriminative and hedonic ratings of a wide range of different food and drink products. Such product-intrinsic auditory contributions to food perception and consumer behaviour are undoubtedly important.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al [28] conducted a study measuring the relative influence of both extrinsic and intrinsic factors. In a mixed model design, participants tasted samples of apple-elderflower nectars under different visual (looking at a pink or pale-yellow rectangle on an iPad screen) and auditory (listening to bitter or sweet soundtrack) conditions.…”
Section: Combining Intrinsic and Extrinsic Influencesmentioning
confidence: 99%